(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
This paper focuses on the control and management of water resources displayed by one of the major Milanese hospitals in the Middle Ages. Since the 13th century, the ospedale del Brolo had increased its properties in the Lodigiano: this paper aims at explaining the main features of the area affected by these investments, and the rights held by the hospital.